A novel TNFR2 agonist peptide for the expansion of CD4+Foxp3+ regulatory T cells - Liao, Ping; Chen, Zhonghao; Gao, Yang; Yang, Yang; Chen, Yibo; Chen, Jiamin; Wang, Yiru; Chou, Chon-Kit; Zhang, Shaoyi; Chen, Xin (Frontiers in Immunology, 2025)
CD4+Foxp3+ regulatory T cells (Tregs) are essential for maintaining immune tolerance, and selective expansion of Tregs via TNFR2 signaling represents a promising therapeutic approach for autoimmune and inflammatory diseases. Here, we report the identification and characterization of UMR2-705, a novel TNFR2 agonist discovered through phage display screening. In vitro, peptide UMR2–705 selectively promoted Treg proliferation in both human peripheral blood mononuclear cells and murine CD4+ T cell cultures without stimulating conventional CD4+ effector or CD8+ T cells. This effect was abrogated by the TNFR2-specific blocking antibody TR75-54.7, indicating its TNFR2 dependency. In vivo, administration of peptide UMR2–705 expanded Tregs in murine spleen and lymph nodes, attenuated LPS-induced systemic cytokine release (IL-6, TNF-α, IL-17A) in serum, and preserved immune homeostasis during systemic inflammation through TNFR2-dependent modulation of the regulatory compartment. Transcriptomic profiling revealed activation of TNFR2-associated signaling and upregulation of immune-regulatory pathways. These findings identify peptide UMR2–705 as a selective, peptide-based TNFR2 agonist with potent Treg-expanding and anti-inflammatory activities, supporting its potential as a therapeutic candidate for autoimmune and inflammatory disorders.